Сезонний ритм росту і розвитку низькорослих сортів Iris hybrida hort. в умовах Лісостепу України - Skrypka, G.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
Phenological development data of 24 dwarf varieties of Iris hybrida hort. plants in the conditions of Ukrainian Forest-Steppe are analyzed. The dependence of phenological phases on weather conditions is determined.